Making Food-Systems Policy for Local Interests and Common Good - Lind, Colene J.; Reeves, Monica L. (Frontiers in Communication, 2021)
The unjust distribution of poor health outcomes produced via current U.S. food systems indicates the need for inclusive and innovative policymaking at the local level. Public health and environmental organizers are seeking to improve food environments from the ground up with locally driven policy initiatives but since 2010 have increasingly met resistance via state-government preemption of local policymaking power. This analysis seeks to understand how political actors on both sides of preemption debates use rhetorical argumentation. In doing so, we offer insights to the meaning-making process specific to food systems. We argue that advocates for local food-system innovations are forwarding understandings of food and community that contradict the policy goals they seek. We offer suggestions for local food and environmental advocates for adjusting their arguments.